2011
DOI: 10.1253/circj.cj-11-0095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of N-Terminal pro-B-Type Natriuretic Peptide in Patients With Acute Coronary Syndromes Undergoing Left Main Percutaneous Coronary Intervention

Abstract: Background: Patients undergoing acute left main (LM) coronary artery revascularization have a high mortality and natriuretic peptides such as N-terminal pro-B-type (NT-proBNP) have been shown to have prognostic value in patients with acute coronary syndromes. The present study looked at the prognostic value of NT-proBNP in these patients. Methods and Results:We studied all consecutive patients undergoing acute LM coronary artery percutaneous coronary intervention between January 2005 and December 2008 in whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The prognostic value of natriuretic peptides has been established in many different scenarios. 16 17 Comorbidities, in particular COPD and CKD, have been found to be associated with worse prognosis in patients undergoing transcatheter aortic valve implantation. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of natriuretic peptides has been established in many different scenarios. 16 17 Comorbidities, in particular COPD and CKD, have been found to be associated with worse prognosis in patients undergoing transcatheter aortic valve implantation. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that plasma levels of natriuretic peptides such as B-type natriuretic peptide (BNP) and NT-proBNP have a robust relationship with prognosis in patients with NSTE-ACS (10)(11)(12). Furthermore, previous studies have demonstrated that increased NT-proBNP levels in patients with NSTE-ACS are independently associated with the presence of more complex and severe coronary lesions (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…B-type natriuretic peptide and its more stable counterpart, N-terminal pro-B-type natriuretic peptide (NT-proBNP), have shown great promise in this area, 6) covering a range of acute coronary syndromes. 7) At the same time, the emerging new peptides may also become clinically useful in the future. Stromal cell-derived factor-1 (SDF-1, also known as CXCL12), a constitutively expressed chemokine, has attracted much attention in the treatment of ischemic diseases.…”
mentioning
confidence: 99%